FRI0684 Early treatment with methotrexate improves all-cause and cardiovascular survival among an inception cohort of seniors with rheumatoid arthritis. (15th June 2017) - Widdifield, J; Paterson, JM; Huang, A; Bernatsky, S; ,
Abstract : Background: We previously observed that incident RA patients have an increased risk of all-cause and cardiovascular disease (CVD) mortality relative to the general population in Ontario. 1 Objectives: To evaluate the effect of treatment and other factors on all-cause and CVD mortality among incident senior RA patients. Methods: We studied incident RA patients within the population-based Ontario Rheumatoid Arthritis Database (ORAD) who were diagnosed after their 65th birthdate (ensuring comprehensive drug coverage) between 2000 and 2013. Patients are included in ORAD if they received 3 physician billing RA diagnosis codes (with at least one provided by a MSK specialist) over 2 yrs OR at least 1 hospital RA diagnosis code. All patients were followed from cohort entry (when all case definition criteria were met) until death, out-migration, or end of study period (Dec 2013). Two multivariable Cox regression models were performed to estimate hazard ratios (HRs) for each outcome (all-cause and CVD mortality, separately), exploring the effects of both baseline/early treatment (within the year preceding index date) and time-varying medication exposures over the entire duration of follow-up (for methotrexate, other DMARDs, anti-TNFs, COXIBS, NSAIDs, glucocorticosteroids, statins, antihypertensives), baseline comorbidities (within 3 yrs prior to index date), time-varying development of extra-articular manifestations (as proxy for disease severity), healthcare use, and demographics (age, sex, rurality, SES). Results: 28, 172 incident RA patients were followed for 141, 072 person years. During follow-up, 8, 848 (31%) patients died with 1, 419 (5%) deaths due to CVD, corresponding to an all-cause rate of 62.7 deaths (95% CI 61.4, 64.0), and 10.1 deaths due to CVD (95% CI 9.5, 10.6) per 1, 000 patient-years, respectively. In our multivariable analysis focused on all-cause mortality, early treatment with methotrexate [HR 0.90 (95% CI 0.85, 0.96)] and other DMARDs [HR 0.92 (95% CI 0.87, 0.97)] were associated with a lower mortality risk. For CVD mortality, early treatment with methotrexate was associated with lower risk estimates [HR 0.71 (95% CI 0.60, 0.83)], which was not clearly seen with other DMARDs [HR 0.94 (95% CI 0.82, 1.08)]. Use of COX-II inhibitors and NSAIDs at baseline were associated with lower HR for all-cause and CVD mortality risk, though we were unable to detect clear associations with greater use during follow-up. Greater cumulative exposure to glucocorticosteroids, comorbidities, and extra-articular manifestations of RA were associated with increasing risk of all-cause and CVD mortality. Conclusions: Patients with early exposure to methotrexate had a lower risk of all-cause and CVD mortality. Our findings support the hypothesis that early treatment, by reducing inflammation, may help improve survival in RA. However, residual confounding cannot be ruled out. References: Widdifield J, et al. Risk of Vascular Mortality in Seniors with New-Onset Rheumatoid Arthritis. Arthritis Rheumatol 2016; 68 (suppl 10). Disclosure of Interest: None declared